The Students Difficulties in Understanding of Active to Passive Voice at X Tm1 SMKN 2 Panyabungan - lubis, Arjun Lubis (Pascasarjana Universitas HKBP Nommensen, 2023)
Grammar is a study about how to make and arrange the sentence. It is an integral part of languages and is very important for the learner. Moreover, the active and passive voice form should be studied to improve our English skills. However, presently students' are sometimes uninterested in the concept of active and passive voice form. This study aims to determine the high substantial the students' obstacle in transforming active to passive voice form at X TM1 SMKN 2 Panyabungan. This research conducted a qualitative way, the source taken at X1 TM SMKN 2 Panyabungan. Data collection is observation, interviews, and documentation techniques. The analysis results reveal the high dominant students' obstacles in determining the subject, using verb3, putting verb be, and obstacles found in the past continuous form. Based on this research finding, the researcher decides that few students' have an adequate understanding of passive voice. However, more students require extra effort to learn and practice grammar to be master and capable of active and passive voice form. Keyword: Analysis, Students' Difficulties, Active and Passive Voice